Swiss Household Energy Demand Survey: Past experiences and new perspectives - Mehdi Farsi; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2024)
This paper is intended as a reference document for the users of the Swiss Household Energy Demand Survey (SHEDS). We outline the survey's objectives, provide a description of its structure and design, and showcase a selection of potential applications. SHEDS has been fielded annually between 2016 and 2021. Since 2021, the survey is planned every second year until 2029, resulting in a total of ten waves over a fourteen-year period. While presenting a brief history of SHEDS and its utilization in the past, we discuss new perspectives of data requirements for energy research in Switzerland. We also provide some pathways for achieving a wider usage by the energy-research community in particular energy-system modelers.
Keywords: 330